Adherence to the Australian National Inpatient Medication Chart: the efficacy of a uniform national drug chart on improving prescription error. Issue 5 (8th May 2012) - Atik, Alp
Abstract: Background  In 2006, the National Inpatient Medication Chart (NIMC) was introduced as a uniform medication chart in Australian public hospitals with the aim of reducing prescription error. Purpose  The rate of regular medication prescription error in the NIMC was assessed. Methods  Data was collected using the NIMC Audit Tool and analyzed with respect to causes of error per medication prescription and per medication chart. The following prescription requirements were assessed: date, generic drug name, route of administration, dose, frequency, administration time, indication, signature, name and contact details. Findings  A total of 1877 medication prescriptions were reviewed. 1653 prescriptions (88.07%) had no contact number, 1630 (86.84%) did not have an indication, 1230 and 675 (35.96%) used a drug's trade name. Within 261 medication charts, all had at least one entry, which did not include an indication, 258 (98.85%) had at least one entry, which did not have a contact number and 200 (76.63%) had at least one entry, which used a trade name. Discussion  The introduction of a uniform national medication chart is a positive step, but more needs to be done to address the root causes of prescription error.